2015
DOI: 10.1111/iep.12139
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide imidacloprid influences cognitive functions and alters learning performance and related gene expression in a rat model

Abstract: The potential toxic effects of several pesticides, including imidacloprid on non-target organisms have not been clearly established. Also, the chronic effects of non-toxic doses on cognitive function in mammals are unknown. In this study, the effects of different doses of imidacloprid on learning and memory of infant and adult rats were evaluated, and the expressions of genes synthesizing proteins known to be associated with learning in brain tissues were also documented. 0.5, 2 and 8 mg/kg doses of imidaclopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 25 publications
5
30
0
Order By: Relevance
“…In addition, IMI was reported to induce sensorimotor impairments in the offspring after single high toxic dose (337 mg/kg) in pregnant rats 28 . In separate groups of infant and adult rats, 2–8 mg/kg IMI given daily for 3 months impaired spatial learning and memory in the Morris water maze task 29 , a finding consistent with another study in rats using the neonicotinoid clothianidin 30 .…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, IMI was reported to induce sensorimotor impairments in the offspring after single high toxic dose (337 mg/kg) in pregnant rats 28 . In separate groups of infant and adult rats, 2–8 mg/kg IMI given daily for 3 months impaired spatial learning and memory in the Morris water maze task 29 , a finding consistent with another study in rats using the neonicotinoid clothianidin 30 .…”
Section: Introductionsupporting
confidence: 86%
“…In terms of experimental design, the study most similar to the present study was conducted by Kara et al . 29 . This group administered IMI to infant and adult rats at 2–8 mg/kg daily for 3 months via the oral route, and conducted a single behavioral test, the Morris water maze where the treated rats displayed impaired spatial learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing evidence to the contrary [11,12,13,14,15,16,17,18,19], and consideration of some neonicotinoid metabolites showing high affinities for mammalian nAChRs [3], suggests that neonicotinoids have potential developmental neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational administration of clothianidin induces behavioral disorders in F1 mice [14] and exposure to clothianidin and other stress causes behavioral and reproductive abnormalities in male mice [15]. Exposure to IMI alters learning performance and related gene expression in infant and adult rats [16]. Recently, Sano et al reported that exposure to low dose ACE in utero and through lactation induces abnormalities in socio-sexual and anxiety-related behaviors in male mice [17].…”
Section: Introductionmentioning
confidence: 99%
“…When the federal government banned some uses of OP pesticides, manufacturers responded by expanding the use of neonicotinoid and pyrethroid pesticides. Evidence is emerging that these widely used classes of pesticides pose a threat to the developing brain ( Kara et al 2015 ; Richardson et al 2015 ; Shelton et al 2014 ).…”
Section: A Call To Actionmentioning
confidence: 99%